2022
DOI: 10.1002/rth2.12628
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of recombinant factor XIII‐A2 in congenital factor XIII deficiency: Real‐world evidence

Abstract: Background Regular factor XIII (FXIII) prophylaxis is standard treatment for congenital FXIII A‐subunit deficiency (FXIII‐A CD). Recombinant factor XIII‐A 2 (rFXIII‐A 2 ) was extensively evaluated in the mentor trials. Objective To assess real‐world safety and treatment effectiveness of rFXIII‐A 2 prophylaxis from the mentor 6 trial. Patients/Methods mentor 6 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…FXIIID concentrate is also the treatment of choice for women with FXIIID during gestation, although there is controversy regarding the dosage and intervals of administration [ 39 ]. Finally, recombinant factor XIII (rfXIII) has been proven to be a safe and efficacious treatment for patients with FXIIID and is gaining in popularity as a prophylaxis option [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…FXIIID concentrate is also the treatment of choice for women with FXIIID during gestation, although there is controversy regarding the dosage and intervals of administration [ 39 ]. Finally, recombinant factor XIII (rfXIII) has been proven to be a safe and efficacious treatment for patients with FXIIID and is gaining in popularity as a prophylaxis option [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of medications is available to manage FXIII deficiency, including FFP, SD-FFP, cryoprecipitate, and a pdFXIII concentrate. However, recombinant FXIII (rFXIII-A2) is preferred when available in cases with FXIII A-subunit defects (95% of all deficient cases) owing to the small infusion volume, low risk of transfusion-associated adverse events, and more precise dosing [ 81 , 82 ]. Based on the MENTOR 2 study, a prospective multi-center observational study, a recommended prophylactic dosage of rFXIII every 4 weeks is 35 IU/kg [ 83 ].…”
Section: Fxiii Deficiencymentioning
confidence: 99%
“…94 Several recent studies have since been performed and shown the safety of this product for prophylaxis and on-demand therapy. [95][96][97] The last and only curative therapeutic option for congenital FXIII deficiency is gene therapy. Although gene therapy has a long history in hemophilia A and B, it has not yet been used in rare bleeding disorders.…”
Section: Management Of Factor XIII Deficiencymentioning
confidence: 99%